Russian forests show strong potential for young forest growth - Christopher S. R. Neigh; Paul M. Montesano; Joseph O. Sexton; Margaret Wooten; William Wagner; Min Feng; Nuno Carvalhais; Leonardo Calle; Mark L. Carroll (Communications Earth & Environment)
Abstract Climate warming has improved conditions for boreal forest growth, yet the region’s fate as a carbon sink of aboveground biomass remains uncertain. Forest height is a powerful predictor of aboveground forest biomass, and access to spatially detailed height-age relationships could improve the understanding of carbon dynamics in this ecosystem. The capacity of land to grow trees, defined in forestry as site index, was estimated by analyzing recent measurements of canopy height against a chronosequence of forest stand age derived from the historical satellite record. Forest-height estimates were then subtracted from the predicted site index to estimate height-age growth potential across the region. Russia, which comprised 73% of the forest change domain, had strong departures from model expectation of 2.4–4.8 ± 3.8 m for the 75th and 90th percentiles. Combining satellite observations revealed a large young forest growth sink if allowed to recover from disturbance.